Efeito da granulometria do abrasivo no desgaste de bombas centrífugas submersíveis - Sabia, Marcelo Gouveia (2015)
Electrical submersible pumping (ESP) is one of the artificial oil lifting methods employed in wells that do not have enough energy to raise the oil naturally to the surface. These pumps work in harsh conditions when pumping water mixed with gases and sand particles. Sand production causes losses in this operation, such as loss of efficiency and critical damage to internal parts. In this study, the effects of the abrasive particle size of sand on the wear of electrical submersible pumps were evaluated. Two pumps were tested, one using sand with an average diameter of 225 m and another using extra-fine sand with an average diameter of 70 m. During the tests, the pump performance curve and its vibration were monitored. Additionally, the bearing clearances and masses of the rotors and diffusers were measured before the beginning and after the end of the tests. The results showed that the worst operating conditions occur when sand of smaller grain sizes was used, since it enhances the bearing wear that leads to a faster radial instability. It was also observed that using abrasive particles of greater sizes leads to high erosive wear, especially in diffusers. In the diffuser region with the thinner cross section the most pronounced erosive wear was noticed.